Pengaruh Kompetensi & Masa Kerja Terhadap Pengembangan Karir Pada PT Air Minum Giri Menang (Perseroda) Mataram - Marlina, Febria Nurmelia; Ihyani, Layali; Marswandi, Ega Dwi Putri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the effect of competence and tenure on employee career development at PT Air Minum Giri Menang (Perseroda) Mataram. A quantitative approach with a survey method was employed, involving 50 respondents. Data analysis was conducted using multiple linear regression through SPSS version 22. The results indicate that competence and tenure significantly and positively affect employee career development, both partially and simultaneously. Competence directly enhances professionalism and performance, while tenure contributes to increased experience and skills. The determination coefficient reveals that 84.6% of career development is influenced by these variables, while the remaining 15.4% is affected by other factors not examined in this study. This research highlights the importance of managing competence and leveraging tenure to optimize career development in corporate settings.